Bringing Microfinance Services to the Poor : Crediamigo in Brazil - Sanchez, Susana M.; Sirtaine, Sophie; Valente, Rita (World Bank, Washington, DC, 2012)
Among policymakers and economists, there is a widely held perception that microenterprises1 face severe financing shortages that limit their growth opportunities. Resolving the problems of access to finance as well as the high cost of financing has become the main objective of many government programs. With a view to increasing access to credit for microenterprises in the Northeast Region of Brazil, the World Bank has supported Banco do Nordeste's CrediAmigo microfinance program since 1997. This note describes how Banco do Nordeste initiated CrediAmigo as part of its restructuring strategy and how the program has expanded to become the largest microfinance provider in Brazil. To date, many lessons have emerged, both from CrediAmigo and the World Bank project that supports the program. Brazilian private banks and non-bank financial institutions offer a variety of credit products targeted to micro and small enterprises. These products typically carry very high interest rates and require collateral. Banking networks also leave many areas, particularly poor and remote regions in the Northeast and North of Brazil, underserved. About 57 percent of all municipalities in these regions have no access to a bank branch, compared to a national average of around 30 percent. Although in many other Latin American countries, microfinance institutions have been able to partially fill the gap left by larger institutions, in Brazil, only a small fraction of the potential demand for microfinance appears to be satisfied by the current supply.